2014
DOI: 10.1108/jcs-02-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Supporting early learning for children under three: research and practice

Abstract: Purpose – The purpose of this paper is to review the literature on young children's learning at home and in early childhood settings, in order to identify key caregiving practices which support the learning and development of children under three. Design/methodology/approach – Starting with well-known reviews carried out in England, the USA, Australia and New Zealand, the authors searched the literature for evidence of the developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…First, it seems clear that the field would benefit from a comprehensive quality framework that can help organize the varying definitions, measures, and processes that make up the current landscape of home‐visiting quality research. This work should build on and expand existing frameworks specific to home visiting (Daro, ; Korfmacher et al., ) and draw from the considerable work to define and measure quality in other fields such as early childhood education and early intervention (La Paro, Thomason, Lower, Kintner‐Duffy, & Cassidy, ; Layzer & Goodson, ; Mathers, Eisenstadt, Sylva, Soukakou, & Ereky‐Stevens, ). An important first step will be to synthesize what we already know.…”
Section: Where To Next For Home‐visiting Quality?mentioning
confidence: 99%
“…First, it seems clear that the field would benefit from a comprehensive quality framework that can help organize the varying definitions, measures, and processes that make up the current landscape of home‐visiting quality research. This work should build on and expand existing frameworks specific to home visiting (Daro, ; Korfmacher et al., ) and draw from the considerable work to define and measure quality in other fields such as early childhood education and early intervention (La Paro, Thomason, Lower, Kintner‐Duffy, & Cassidy, ; Layzer & Goodson, ; Mathers, Eisenstadt, Sylva, Soukakou, & Ereky‐Stevens, ). An important first step will be to synthesize what we already know.…”
Section: Where To Next For Home‐visiting Quality?mentioning
confidence: 99%
“…In a study with Labella, Engel (2011) found significantly low levels of curiosity within classrooms and attributed this to the focus within schools around attainment of skills, the pressure of testing and assessment and concluded that education was focussed on mastery rather than enquiry. Although this was a study of older children, as outlined above, the documentary analysis of the Early Years Foundation Stage revealed few explicit references to curiosity, even though children are primed to be curious (Mathers et al, 2014). The lack of focus on curiosity as a key aspect of children's learning within the EYFS may indicate why practitioners do not focus on this in practice.…”
Section: Curiositymentioning
confidence: 97%
“…This focus indicates that lifelong learning can have a positive impact upon the poverty rates which continue to rise within the UK (Joseph Rowntree Foundation, 2017). Lifelong learning has particular relevance to this research as the earliest years lay its foundations (Mathers, Eisenstadt, Sylva, Soukakou and Ereky-Stevens, 2014).…”
Section: What Is the Issue? Lifelong Learningmentioning
confidence: 99%
See 2 more Smart Citations